Males and females with scleroderma: A comparative study in a Brazilian sample - Matheus Costa; Igor Jorge; Patricia Martin; Renato Nisihara; Thelma Skare (Archives of Rheumatology, 2023)
Objectives: This study aimed to evaluate the clinical and serological profile in systemic sclerosis (SSc) by comparing females and males. Patients and methods: This retrospective study was conducted with 215 SSc patients (193 females, 22 males; mean age: 50.1±14.5 years; range, 16 to 88 years) between September 2005 and September 2020. Disease severity was calculated by the Medsger severity score. Males and females were compared for clinical and serological markers. Results: Females more frequently had esophageal involvement (p=0.003), telangiectasias (p=0.03), and antinuclear antibodies (p=0.04). Males more frequently had fingertip scars (p=0.03), digital ulcers (p=0.006), and a worse median Medsger severity score (6 in males vs. 4 in females, p=0.05). Conclusion: In the studied sample, males had more severe disease than females with greater repercussions in periferic circulatory system.